COMPARISON OF THE PERFORMANCE OF A SUPPLY CHAIN UNDER REBATE AND OPTION CONTRACTS - Gomez-Padilla, Alejandra; Mishina, Tsutomu (Brazilian Journal of Operations & Production Management, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->The objective of this document is to compare the performance of the companies forming a dyadic supply chain, and for the chain as a single unit, under two types of contracts: option and rebate. The performance is measured in economic terms (benefits and costs) and in physical units (inventory held and unsatisfied demand). The results will help to identify which is the better contract for a given set of parameters. Under an option contract, the retailer orders a quantity of units and has a right to modify his order (increase or decrease) by buying the option premium in advance from the supplier. Under a rebate contract, the supplier offers a rebate for the units ordered over a certain number of units previously fixed. With an option contract, the retailer reserves a number of units from the supplier and, after receiving more information about demand, he will pass his final order. With a rebate contract, the retailer will decide from the beginning the number of units to order knowing the rebate condition (price and quantity). First the theoretical bases are introduced for each contract, next both models are compared by simulation. The simulation plan is presented and the results are discussed.